Pendidikan Karakter Menurut Imam Nawawi dan Aplikasinya dalam Kehidupan - Wanty Khaira; Irman Siswanto (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Character can be interpreted as character, character, psychological traits, morals or character that distinguishes one person from another. One of the works of Imam Nawawi ra. is the Book of Riyadhus Shalihin which is a very famous book in the Islamic world. This book has been used as a guide for years among scholars, students and students of religious knowledge in parts of the Islamic world. The contents of the work of Imam Nawawi ra. This is able to organize and grow the strength of a big soul in someone in worshiping Allah SWT, the creator of the universe, because worshiping Allah SWT can lead a person to goodness and happiness. The purpose of this study was to determine the application of character education according to Imam Nawawi ra. within the Madrasah Aliyah environment in Aceh. This study uses a qualitative method. This research was conducted by collecting the necessary library data, especially the essay of Imam Nawawi ra. Data collection also uses observations and interviews with the community in the Madrasah Aliyah environment in Aceh to obtain character education application data according to Imam Nawawi ra. The results showed that the values of character education according to Imam Nawawi ra. related to Commandments, related to Warnings and related to Instructions and character with Allah and with Creatures. For the community in the Madrasah Aliyah environment in Aceh, they have applied character education that has been formulated by Imam Nawawi ra.as the regulations that apply in the Madrasah environment